Tinjauan Kualitas Layanan Internal di Instalasi Rekam Medis Rumah Sakit Islam Sultan Agung Semarang - Novita Pratiwi; Zefan Adiputra Golo; Subinarto Subinarto (Indonesian of Health Information Management Journal (INOHIM), 2022)
AbstractInternal service quality affects officer satisfaction. The existence of quality internal services will increase employee satisfaction so that work results can be optimal. It is necessary to look at the extent to which medical record officers perceive the quality of internal services in the Medical Record Work Unit. The results of the preliminary study found that the hospital management had never conducted a survey of officers to assess the quality of internal services received by officers. In addition, the results of the performance assessment of officers at the medical record installation in 2018–2020 have fluctuated. The aim of this study was to determine the quality of internal services received by officers at the medical record installation of RSI Sultan Agung Semarang. This type of research is descriptive quantitative survey method. The research sample was all officers at the medical record installation as many as 41. The data were analyzed using descriptive analysis. The results of the research are internal service quality from the employee empowerment aspect in the high category, which is equal to 90%, the internal communication aspect is in the good category, which is equal to 98%, the teamwork aspect is in the good category, which is equal to 95%, the award aspect is in the high category, which is equal to 98%. , aspects of education and training in the sufficient category that is equal to 93%. Medical record installations need to improve the quality of internal services for officers, especially from the aspect of employee empowerment, as well as aspects of education and training by providing facilities, education and training to help officers complete their work optimally.Keyword: Internal Service Quality, Employee Empowerment, Internal Communication, Teamwork,  Education and Training  AbstrakKualitas layanan internal berpengaruh terhadap kepuasan petugas. Dengan adanya layanan internal yang berkualitas akan meningkatkan kepuasan petugas sehingga hasil pekerjaan dapat optimal. Perlu dilihat sejauh mana persepsi petugas rekam medis terhadap kualitas layanan internal di Unit Kerja Rekam Medis. Hasil studi pendahuluan menemukan pihak manajemen rumah sakit belum pernah melakukan survey kepada petugas untuk menilai bagaimana kualitas layanan internal yang diterima oleh petugas. Selain itu hasil penilaian kinerja petugas di instalasi rekam medis tahun 2018–2020 mengalami fluktuatif. Tujuan penelitian untuk mengetahui kualitas layanan internal yang diterima oleh petugas di instalasi rekam medis RSI Sultan Agung Semarang. Jenis penelitian ini deskriptif kuantitatif dengan metode survey. Sampel penelitian adalah seluruh petugas di instalasi rekam medis sebanyak 41. Data dianalisis menggunakan analisis deskriptif. Hasil penelitian yaitu kualitas layanan internal dari aspek pemberdayaan pegawai dalam kategori tinggi yaitu sebesar 90%, aspek komunikasi internal dalam kategori baik yaitu sebesar 98%, aspek kerja sama tim dalam kategori baik yaitu sebesar 95%, aspek penghargaan dalam kategori tinggi yaitu sebesar 98%, aspek pendidikan dan pelatihan dalam kategori cukup yaitu sebesar 93%. Instalasi rekam medis perlu meningkatkan kualitas layanan internal bagi petugas, khususnya dari aspek pemberdayaan pegawai, serta aspek pendidikan dan pelatihan dengan memberikan sarana, pendidikan dan pelatihan untuk membantu petugas menyelesaikan pekerjaannya dengan optimal.Kata Kunci: Kualitas Layanan Internal, Pemberdayaan Pegawai, Komunikasi Internal, Kerjasama Tim, Pendidikan dan Pelatihan